Antioxidant and iron chelating potential of Pongammia pinnata and its role in preventing free radical induced oxidative damage in plasmid DNA - Bibhabasu Hazra; Rhitajit Sarkar; Santanu Biswas; Nripendranath Mandal (International Journal of Phytomedicine, 2011)
Reactive oxygen species (ROS) and free radical-mediated reactions are involved in degenerative or pathological processes. Antioxidants are believed to play an important role in preventing chronic diseases by reducing the oxidative damage to cellular components caused by ROS. In the present study, Pongamia pinnata leaf (PPL), seed (PPS), and flower (PPF) were investigated for their total phenolic and flavonoid contents, antioxidant activity by ABTS and DPPH method, scavenging activities for different free radicals such as hydroxyl, superoxide, nitric oxide, hydrogen peroxide, peroxynitrite, singlet oxygen, hypochlorous acid, the inhibition of lipid peroxidation in mice brain homogenate, reducing power, iron chelating and protection of DNA damage caused by free radicals. PPL showed the best antioxidant activity compared to both PPS and PPF. The extract of PPL possessed most potent activity compared to other extracts in scavenging assay for singlet oxygen, hydroxyl radical, superoxide radical and nitric oxide radical. PPF exhibited strongest inhibitory activity against hypochlorous acid and peroxynitrite anion among these three extracts. PPL was the best amongst three to inhibit lipid peroxidation and Fe2+-ferrozine complex formation. PPL was also found effective in protecting plasmid DNA nicking at lower concentration while both PPS and PPF did the same at higher concentration. PPL presented highest content of phenolics and flavonoids among these three extracts. The present results show that Pongammia pinnta acts as an antioxidant, iron chelator and protector of oxidative DNA damage.